Change of the metabolomic profile during short‐term mononuclear cell storage. Issue 2 (4th January 2017) - Steininger, P. A.; Strasser, E. F.; Ziehe, B.; Eckstein, R.; Rauh, M.
Abstract : Background and Objectives: Short‐term storage of leukapheresis products used for immunotherapeutic mononuclear cell (MNC) products is a frequent event. The analysis of time‐related metabolic patterns enables the characterization of storage‐related effects in MNCs and the hypothesis‐based optimization of the MNC medium. Materials and Methods: The MNC products from seven leukapheresis procedures were stored within a closed bag system for 48 h. Concentrations of amino acids, biogenic amines, phospho‐ and sphingolipids and hexoses in the medium were measured by targeted metabolomics. The viability of MNC subpopulations was assayed by Annexin V (AnV) and JC‐1 staining. Results: Glucose depletion and a significant change of the acylcarnitine profile are early events within the first 24 h of storage. In contrast, for most amino acids, the maximum increase was observed at 48 h of storage as mirrored by an increase in the amino acid levels by a mean factor of 1·2 (1·3, 2·0) after 6 h (24 h, 48 h, respectively). This was except for the concentrations of glutamine and lysine, which did not change significantly. The taurine concentration showed a twofold increase within the first 24 h and remained constant thereafter. The steepest increase in AnV + and 7‐AAD + CD4 + T cells was found between 24 and 48 h. Conclusion: The time–course of apoptosis and metabolic patterns in the MNC products demonstrate that 24 h of storage is a decisive time‐point, as afterwards key metabolic pathways showed nonlinear detrimental changes. Optimization of storage by supplementation of specific substrates demands therefore an early intervention.